Osteometric study of human femur - N., Khaleel; Shaik, Hussain Saheb (International Journal of Research in Medical Sciences, 2017)
Skeleton is playing important role in various like Medicine, Forensic sciences, Anthropology etc. Estimation of sex, age, race, stature by skeleton and the presence of disease is discovered by Krogman and Iscan (1986). Sex is determined after death by skeletal remains of that individual by some forensic anthropologists with the help of pelvis, skull and long bones. The study was undertaken in 50 femurs for measuring epicondylar breadth, Neck shaft angle, transverse and vertical diameter of head. The results were the average meanepicondylar breadth was 75.6 ± 6.06mm, mean right epicondylar breadth was 73.96 ± 4.99mm and left it was 76.35 ± 7.0mm. The average mean neck shaft angle was 125.3 ± 6.50mm, mean right neck shaft angle was 124.44 ± 5.7mm and left it was 126.3 ± 7.33mm. The average mean transverse diameter of head was 37.86 ± 3.06mm, mean right transverse diameter of head was 37.74 ± 3.05mm and left it was 38.00 ± 3.13mm. The average mean vertical diameter of head was 42.24 ± 3.53mm, mean right vertical diameter of head was 41.63 ± 3.09mm and left it was 42.96 ± 3.92mm, Neck shaft angle ranges from a minimum of 106° to maximum 135° with a mean value of 125.3°. The knowledge of osteometric values is helpful to anthropological and forensic practice.